Hans Hofmann - Goodman, Cynthia (New York, N.Y. Abbeville Press Publishers, 1986)
Traces the career of the German-born artist, shows paintings from each period of his work, and discusses Hofmann's technique.
European heritage -- California, New York, Provincetown -- Breakthrough -- The fifties -- The late paintings -- Artist's statements -- Notes on technique.
Includes bibliographical references (pages 124-126) and index.
Keywords: Hofmann, Hans -- 1880-1966.; Painters -- United States -- Biography; Art teachers -- United States -- Biography